The importance of training towards better service productivity: A case of 3-star hotels in Kuantan / Norazlan Anual and Kamisah Ariffin - Anual, Norazlan; Ariffin, Kamisah (2004)
The most critical resource in an organization is the workforce. It is the staff that directly uses the other resources to sell, to make, to process, or to provide quality of service. How well the resources of money, materials and equipment are used depends largely upon the human resources. Therefore, as claimed by De Cenzo (1994) [2], every organization needs well-trained and experienced people to perform the activities that must be completed. Thus, there is a continual need for the process of staff development and training to fulfill the organizations needs (Steward 1993) [12]. This paper seeks to find out the importance of training in developing skills of rank and file employees of 3-star hotels in Kuantan area towards a better service productivity.